Translation of the Word “Bagus” in Folklore Asal Mula Kata Babah Using Google Translate - Rafika Zahra (ITScience (Information Technology and Science), 2023)
Translating cultural terms is a study that should be explored further, particularly in translating cultural words using machine translation. Google Translate is a machine translation that was widely used by people to translate one language into another language. This study only focused on the cultural word